Mineral concentrations of grain of bread wheat landraces originated from eastern Anatolia of Turkey - Kokten, Kagan; Akcura, Mevlut (Progress in Nutrition, 2018)
The objectives of this research were to investigate the interrelationships among some mineral concentrations (Fe, Zn, B, Mn, Cu, Mo, K, Mg and Ca) in grain and to evaluate different eastern Anatolian bread landraces with application of the genotype × trait (GT) biplot methodology in visualizing research data. 69 bread wheat genotypes (67 pure lines and 2 cultivars). Fe, Zn, B, Mn, Cu, Mo, K, Mg and Ca contents of bread wheat genotypes changed at the levels between 32.54 and 51.25 mg kg-1, 23.00 and 37.16 mg kg-1, 6.62 and 14.67 mg kg-1, 30.17 and 50.00 mg kg-1, 4.04 and 6.88 mg kg-1, 0.88 and 1.23 mg kg-1, 2.19 and 5.62 g kg-1, 1.04 and 1.72 g kg-1, and 0.37 and 0.55 g kg-1, respectively. Among minerals, B, Zn and Fe concentrations were the most discriminating with the longest vectors from the origin in the biplot. Landraces L10, L48, L2, L55, L17, L14, L36, L16, L53, L22, L32, L53 L65 and Kirik cultivar were the best or the poorest landraces in some or all of the traits since they had the longest distance from the origin of biplot. Among the mineral contents, Fe content was positively correlated with Zn and Mn content. The association of Zn with Mn was positive and significant. B content positive and significant correlated with Mo content. Both Zn and Fe content was negative significant correlated with Ca. The GT biplot method can be used to identify both ideal genotypes and mineral contents in other crops.